Case for diagnosis - Guida Santos; Lourdes Sousa; Teresa Fernandes; Alexandre Joao (Sociedade Brasileira de Dermatologia, 2014)
Cutaneous involvement associated to multiple myeloma varies from 5 to 10% of cases and is infrequently recognized. Cutaneous metastatic plasmacitomas are rare. We present the case of a 72-year-old man with multiple myeloma in complete remission since 2 years ago with cutaneous tumors on the trunk and face. A cutaneous biopsy was consistent with plasmacytoma. The patient was treated with melphalan, prednisolone and radiotherapy. Despite optimal therapeutic response of the lesions, the disease progressed, with the appearance of new extra-cutaneous plasmocytomas. The cutaneous metastatic plasmocytomas were the first sign of progression of the disease.